Physicochemical Characteristics and Soil Suitability for Semi-Irrigated Rice Cultivation in The Tandjile Province of Chad - Issiné, Agoubli; Justin, Kao-mbassi Yerima Keda; Gomoung, Doloum (International Journal of Applied Sciences and Biotechnology, 2024)
A study carried out in Tandjilé-Est, a region located in the South-Central part of Chad, aimed to examine the pedoclimatic and socio-economic parameters that cause the variability of rice yield (Oryza sativa) in an irrigated system. Three sites in the Kabalaye canton were chosen for soil sampling; these are Satégui, Mala and Djongo; in each site, five soil samples were taken. To assess the suitability of irrigated areas, two assessment methods were used on the two types of soils in the study area, including a Vertisol and a Planosol. This assessment shows that Vertisols are suitable for growing rice in an irrigated system, while Planosols are marginal. The main limitation in Planosols is the low nutrient content. To overcome this problem, it is necessary to improve the management of field fertility, rotate crops, and train producers in integrated fertility management and provide them with credit and adequate agricultural equipment. Int. J. Appl. Sci. Biotechnol. Vol 12(4): 180-186.